Contribution to the study of leaf venation of "cerrado" plants Labiatae - Matos, Maria Ermelinda Roque de (Pesquisa Agropecuaria Brasileira, 2014)
The venation patterns of 13 species of Labiatae of the "cerrado" vegetation are given. The species fall into three groups according to venation: brochidodrome, camptodrome and mixed. Two types of marginal venation were noticed: marginal veins parallel to the leaf edges and marginal veins which stop at the leaf edge without running parallel to it. Lignified sheaths around the vascular bundles were found in two species, one arboreal and the other herbaceous.